ANALISIS KESULITAN BELAJAR DALAM MEMAHAMI PERKALIAN DASAR PADA SISWA KELAS 2 SD - Niran, Marlina; Diba Catur Putri, Fara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning basic multiplication is an important competency in early elementary school mathematics. However, in practice, many second-grade students still experience difficulties in understanding the concept of multiplication. This study aims to analyze the forms of student learning difficulties in understanding basic multiplication and the factors that influence them. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the analysis indicate that student learning difficulties include a lack of understanding of the concept of multiplication as repeated addition, limited basic numeracy skills, and low interest and motivation in learning mathematics. In addition, the use of less varied learning methods and the lack of concrete media also hinder student understanding. These difficulties impact students' low ability to solve simple multiplication problems. Therefore, a learning strategy is needed that emphasizes conceptual understanding through the use of concrete media, a contextual approach, and a pleasant learning atmosphere to improve students' understanding of basic multiplication.